2021
DOI: 10.1038/s41598-021-84112-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microalgae cultured in Bold’s Basal medium from freshwater samples, from a high-rise city

Abstract: This study aimed at exploring microalgal heterogeneity from fresh water samples collected from inland water bodies in the heavily built city of Singapore. Culturable pure isolates (n = 94) were subject to an in-house microalgal DNA extraction method and LSU rDNA sequencing. Isolates were analysed for their predominance and distribution. A total of 17 different algal genera were identified (H = 2.8, EH = 0.6), of which Scenedesmus spp. and Chlorella spp. constituted 27.5% and 21.3% of isolates respectively, fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…20 different microalgal strains were isolated from freshwater resources in Pakistan by serial dilution and streak plating and cultured in BBM for maintenance [22]. In a similar study, 94 culturable pure isolates of microalgae were obtained through plating and serial dilution techniques from freshwater sources of Singapore city and maintained in BBM for further characterization [23].…”
Section: Sample Collection Isolation and Culturementioning
confidence: 99%
“…20 different microalgal strains were isolated from freshwater resources in Pakistan by serial dilution and streak plating and cultured in BBM for maintenance [22]. In a similar study, 94 culturable pure isolates of microalgae were obtained through plating and serial dilution techniques from freshwater sources of Singapore city and maintained in BBM for further characterization [23].…”
Section: Sample Collection Isolation and Culturementioning
confidence: 99%
“…In this medium, we were able to isolate thirty different species of green algae. We recognize that some genera are difficult to cultivate in this medium, thus we claim that our study is representative of Gujar Khan's overall green algal biodiversity (Lloyd et al, 2021). The study revealed that sampling areas with varied ecological variables play important role in influencing the distribution and diversity of subaerial algal communities.…”
Section: Cosmarium Crenatummentioning
confidence: 87%
“…The cultures from the third sampling showed an abundance of Chlorella with a dispersed presence of diatoms. Although microalgae are unique to ecological sites of isolation (Lloyd et al, 2021), previous surveys of microalgal genera showed the high domination potentials of Chlorella (Lloyd et al, 2021;Palmer, 1974as cited by Abdel-Raouf, 2012Severes, 2018). However, the varying results may be attributable to the local geographical, climatic, and ecological conditions (Ramachandra et al, 2011).…”
Section: Comparison Of Microalgal Assemblage On Different Sampling Datesmentioning
confidence: 98%